Research on Mechanical Properties and Macroscopic Fracture Evolution of Rock with Different Joint Plane Features - Yongjiang Yu; Jingjing Liu; Pengbo Wang; Yuntao Yang; Shangqing Zhao (Shock and Vibration)
To analyze the safety of geological engineering, experimental research on the mechanical properties of the rock joint plane is critical. In this paper, triaxial compression tests are carried out on rock specimens with the different prefabricated joint planes, including different dip angles, roughness, confining pressure and surrounding rock strength, and the strength characteristics, failure modes, stress evolution laws, and crack propagation laws are revealed. The test results show that when the specimen is damaged, the strain, peak stress, and residual strength all increase with the increase of roughness, confining pressure, and strength of surrounding rock but decrease significantly with the increase of joint plane angle. With the increase of stress, the stress-strain curve shows multiple fluctuations, indicating that the specimen occurs multiple slip-stable phenomena during the loading process. With the increase of the angle, the multiple cracks of the specimen gradually merge, and the cracks are always vertical to the joint plane, showing splitting failure. As the roughness of the joint plane increases, the possibility of the joint plane sliding becomes smaller, and the splitting mode of the specimen develops from multiple fractures to a single fracture. As the strength of the surrounding rock increases, the slope of the stress-strain curve gradually increases, and the splitting mode develops from a small number of single splits to multiple splitting penetration failures. The increase of the confining pressure significantly improves the failure strength of the specimen, and the crack number of the damaged specimen also increases significantly. The research results provide theoretical support for scientific analysis of the stability of underground engineering under the disturbance of fissures or faults.